Modification of human pericardium by chemical crosslinking - Filová, E; Staňková, L; Eckhardt, A; Svobodová, J; Musílková, J; Pala, J; Hadraba, D; Brynda, E; Koňařík, M; Pirk, J; Bačáková, L (Physiological research, 2020)
Autologous and allogenic human pericardia used as biomaterials for cardiovascular surgery are traditionally crosslinked with glutaraldehyde. In this work, we have evaluated the resistivity to collagenase digestion and the cytotoxicity of human pericardium crosslinked with various concentrations of glutaraldehyde in comparison with pericardium crosslinked by genipin, nordihydroguaiaretic acid, tannic acid, and in comparison with unmodified pericardium. Crosslinking retained the wavy-like morphology of native pericardium visualized by second harmonic generation microscopy. The collagenase digestion products were analyzed using SDS-PAGE, capillary electrophoresis, and a hydroxyproline assay. Glutaraldehyde and genipin crosslinking protected the native pericardium efficiently against digestion with collagenase III. Only low protection was provided by the other crosslinking agents. The cytotoxicity of crosslinked pericardium was evaluated using xCELLigence by monitoring the viability of porcine valve interstitial cells cultured in eluates from crosslinked pericardium. The highest cell index, reflecting both the number and the shape of the monitored cells was observed in eluates from genipin. Crosslinking pericardium grafts with genipin therefore seems to be a promising alternative procedure to the traditional crosslinking with glutaraldehyde, because it provides similarly high protection against degradation with collagenase, without cytotoxic effects.
Keywords: Transplants; Masoprocol; reagencia zkříženě vázaná; lidé; Biocompatible Materials; Iridoids; iridoidy; Pericardium; transplantáty; Glutaral; biokompatibilní materiály; taniny; glutaraldehyd; perikard; Cross-Linking Reagents; Tannins; kyselina nordihydroguaiaretová; Humans